Global evidence on profit shifting within firms and across time - Fotis Delis; Manthos D. Delis; Luc Laeven; Steven Ongena (European Commission, Joint Research Centre (JRC), 2023)
We provide estimates of profit shifting for over 2 million firm-year observations in 100 countries over the period 2009-2020. Employing nonparametric estimation techniques within a mainstay model of profit shifting, we examine how profits for both parent and subsidiary firms within a multinational group respond to marginal changes in the composite tax indicator. The key merit of this approach is that it yields firm-year estimates of profit shifting. We find that multinational firms engage in extensive profit shifting by maintaining affiliates in low-tax countries and zero-tax havens. Multinational groups with an ultimate owner in tax havens exhibit the largest responses of profits to the tax incentive. Our comprehensive estimates of global profit-shifting volumes exceed those obtained elsewhere in the literature using firm-level data and are in line with estimates obtained using macro-level data. Our new database opens important avenues to analyse the sources and effects of profit shifting.
Keywords: 330